2015
DOI: 10.1542/peds.2015-0966
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Pediatric Inpatient Experience of Care Measure: Child HCAHPS®

Abstract: CMS uses Adult HCAHPS® scores for public reporting and pay-for-performance for most U.S. hospitals, but no publicly available standardized survey of inpatient experience of care exists for pediatrics. To fill the gap, CMS/AHRQ commissioned the development of the Consumer Assessment of Healthcare Providers and Systems Hospital Survey – Child Version (Child HCAHPS), a survey of parents/guardians of pediatric patients (<18 years old) who were recently hospitalized. This Special Article describes the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(144 citation statements)
references
References 22 publications
2
139
2
1
Order By: Relevance
“…One approach is to instruct all parents on how to report potential errors; the inclusion of an item asking parents whether they were informed of the hospital's error-reporting process in the Child Hospital Consumer Assessment of Healthcare Providers and Systems survey 30 may prompt more hospitals to systematically provide such information to all families. By priming parents to pay attention to safety, hospitals may be able to engage them to help identify errors and perhaps even mitigate those that are potentially harmful.…”
Section: Discussionmentioning
confidence: 99%
“…One approach is to instruct all parents on how to report potential errors; the inclusion of an item asking parents whether they were informed of the hospital's error-reporting process in the Child Hospital Consumer Assessment of Healthcare Providers and Systems survey 30 may prompt more hospitals to systematically provide such information to all families. By priming parents to pay attention to safety, hospitals may be able to engage them to help identify errors and perhaps even mitigate those that are potentially harmful.…”
Section: Discussionmentioning
confidence: 99%
“…25 The final Child HCAHPS Survey instrument has 62 items, including 39 patient experience items (which comprise 18 composite and single-item measures), 10 screening questions, 12 demographic/descriptive items, and 1 open-ended item. We found that hospital-level reliability for our composite and single-item measures would be good to excellent at the recommended sample size of 300, comparable to Adult HCAHPS 26 and reaching recommended levels for comparison.…”
Section: Methodsmentioning
confidence: 99%
“…During the development of the Child HCAHPS Survey, we tested the effects of variables available from the survey and hospitals’ administrative data and identified those that were predictive of responses and also had unequal distributions at different hospitals. 25, 28 In our final model, child covariates are age (<1, 1–4, 5–8, 9–12, ≥13 years) and parent-reported global health status (excellent, very good, good, fair, poor). Parent covariates include age (<25, 25–34, 35–44, ≥45 years); relationship to child (mother, father, other); education (≤8th grade, some high school, high school diploma or general educational development, some college or 2-year degree, 4-year college degree, >4-year college degree); and preferred language (English, Spanish, other).…”
Section: Methodsmentioning
confidence: 99%
“…This tool is used by most major children's hospitals and, like Adult HCAHPS, focuses on aspects of inpatient care that are important for patients and their parents. The pediatric survey contains 62 items that assess the following themes: communication with parents, communication with children, attention to safety and comfort, hospital environment, and global rating [43]. Information is obtained from parents, who act as a proxy for their child in answering questions.…”
Section: The Pediatric Experiencementioning
confidence: 99%